ANTICANCER EFFECTS OF BROCCOLI EXTRACT ON BREAST CANCER CELL LINES: A PHYTOCHEMICAL PERSPECTIVE - KAJAL PARASHAR; MOHAMMAD RASHID KHAN; MINHAJ AHMAD KHAN (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The study aims to evaluate the phenolic content, antioxidant activity, GCMS and LCMS phytochemical profiles, as well as the therapeutic properties of broccoli extract on the breast cancer cells (MCF-7) and the non-cancerous mouse fibroblast cell line, 3T3-L1. Methods: We studied the antibreast cancer effect of the broccoli extract in vitro using human breast cancer cell line MCF-7 and mouse fibroblast cell line 3T3-L1 using the cell cytotoxicity assay, and the percentage of cells that are viable was calculated at varying concentrations and different time incubations, i.e., 24 and 48 h. Furthermore, biochemical estimation was done to check the total phenolic content using Folin–Ciocalteu’s method and antioxidant assays using 2,2-diphenyl-1-picrylhydrazyl and ABTS assays. To check the bioactive profile of the broccoli extract, gas chromatography– mass spectrometry, liquid chromatography–mass spectrometry (LCMS), and high-performance liquid chromatography (HPLC) analyses were done. As sulforaphane is the major bioactive compound of the broccoli, its presence was confirmed by LCMS and HPLC. Results: Broccoli extract was found to be rich in polyphenols and showed a potent number of antioxidants, which states that it reduces the reactive oxygen species production and hence reduces the oxidative stress. It also showed that it decreased cell viability, and the outcomes depended on the dose and time. Conclusion: Based on the reduction of breast cancer cells’ viability, broccoli extract was found to exhibit anticancer effect on MCF-7 cell lines. It has shown that the broccoli extract is rich in antioxidants and highly abundant in polyphenols and anticancer in nature. Further in vivo studies will be done to investigate the anticancer efficacy of the broccoli extract in mice models. This encouraging discovery emphasizes the necessity to investigate broccoli extract’s potential application as a breast cancer treatment.